(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article is devoted to the phenomenon of strategy as a way of working with senses, opens its mechanism, the relationship of processes of meaning to the problem of identity. We analyze the concept of Westernism And Zinoviev revealed the characteristic features of zapadoidov. Features, location, role, functions and problems of modern education in Western countries understandbased on the ideas and A. Zinoveva D. Dzhekobs.V work paid attention to, and America as seen through the eyes of the traveler Zh. Bodriyyara.